1990
DOI: 10.1088/0953-8984/2/35/007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocrystalline anisotropy and first-order magnetisation processes in (Pr1-xNdx)2Fe14B compounds

Abstract: The magnetocrystalline anisotropy of the pseudobinary (Pr1-xNdx)2Fe14B compounds has been measured by using the singular point detection (SPD) technique. The measured temperature and composition dependence of the anisotropy field has been compared with the data obtained in CEF approximations using different sets of (Anm) parameters for Nd2Fe14B and Pr2Fe14B and by considering a linear combination of the anisotropy in the mixed system. The comparison is made by calculating the anisotropy constants, then the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…From this the ground state magnetic moments along the c-axis and in the ab-plane are µ z = 1.71µ B /Nd and µ x = 0.46µ B /Nd, respectively. If the anisotropy energy is calculated using the fitted parameters 43 , the easy axis is predicted to correspond to the c-axis, which is in agreement with that observed in the single crystal susceptibility 29 , and corresponds to the direction of the ordered moment below T 0 .…”
Section: Inelastic Neutron Scattering Measurementssupporting
confidence: 79%
“…From this the ground state magnetic moments along the c-axis and in the ab-plane are µ z = 1.71µ B /Nd and µ x = 0.46µ B /Nd, respectively. If the anisotropy energy is calculated using the fitted parameters 43 , the easy axis is predicted to correspond to the c-axis, which is in agreement with that observed in the single crystal susceptibility 29 , and corresponds to the direction of the ordered moment below T 0 .…”
Section: Inelastic Neutron Scattering Measurementssupporting
confidence: 79%
“…By considering the magnetocrystalline anisotropy energy (E a ), the moment is predicted to lie along the c axis for a negative B 0 2 and the ψ 1 GS. 36 Therefore our CEF model correctly predicts the direction of the observed magnetic moment. From previous studies of the magnetic susceptibility, a CEF scheme with a GS of |± 1 2 was suggested.…”
Section: Inelastic Neutron Scatteringmentioning
confidence: 55%
“…The present results (Figs. [3][4][5][6][7][8][9] indicate that the spin reorientation does not deteriorate the magnetic properties. On decreasing the temperature below ambient: (i) j H C for the alloys investigated increases rapidly; (ii) J r and (BH) max increase for Nd-rich alloys but there is no significant change for Pr-rich alloys.…”
Section: Using Nanophase (Nd/pr)-(fe/co)-b Magnets At Low Temperaturementioning
confidence: 99%
“…The effects of substitutions of rare-earth elements or 3d transition metals on the spin reorientation of Nd 2 Fe 14 B-type compounds in single crystal or sintered magnet forms have been examined extensively [1][2][3]. However, nanocrystalline REFeB alloys have received relatively little attention; notably, no detailed study of the effects of mean crystallite size d g on the spin reorientation has been reported previously.…”
Section: Introductionmentioning
confidence: 99%